2011
DOI: 10.1016/j.aeolia.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Regional and climatic controls on seasonal dust deposition in the southwestern U.S.

Abstract: a b s t r a c tVertical dust deposition rates (dust flux) are a complex response to the interaction of seasonal precipitation, wind, changes in plant cover and land use, dust source type, and local vs. distant dust emission in the southwestern U.S. Seasonal dust flux in the Mojave-southern Great Basin (MSGB) deserts, measured from 1999 to 2008, is similar in summer-fall and winter-spring, and antecedent precipitation tends to suppress dust flux in winter-spring. In contrast, dust flux in the eastern Colorado P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…Greater than normal precipitation in winter months leads to the growth of annual plants can that dramatically reduce wind erosion potential of alluvial sources (MacKinnon et al, 2004;Urban et al, 2009;Reheis and Urban, 2011). Alternatively, high dust emissions are not always correlated to drought, as some of the highest dust fluxes in the last decade occurred in 2005 following a wet winter (Reheis and Urban, 2011). Documented increases in dust flux correspond to both strong El Niño (wet) and La Niña (dry) years (Okin and Reheis, 2002).…”
Section: Heterogeneity Of Emissionsmentioning
confidence: 90%
See 2 more Smart Citations
“…Greater than normal precipitation in winter months leads to the growth of annual plants can that dramatically reduce wind erosion potential of alluvial sources (MacKinnon et al, 2004;Urban et al, 2009;Reheis and Urban, 2011). Alternatively, high dust emissions are not always correlated to drought, as some of the highest dust fluxes in the last decade occurred in 2005 following a wet winter (Reheis and Urban, 2011). Documented increases in dust flux correspond to both strong El Niño (wet) and La Niña (dry) years (Okin and Reheis, 2002).…”
Section: Heterogeneity Of Emissionsmentioning
confidence: 90%
“…Most wind erosion in the Mojave occurs in the winter and spring due to high winds, but vegetation density is highest during this time due to winter moisture (Bach et al, 1996). Greater than normal precipitation in winter months leads to the growth of annual plants can that dramatically reduce wind erosion potential of alluvial sources (MacKinnon et al, 2004;Urban et al, 2009;Reheis and Urban, 2011). Alternatively, high dust emissions are not always correlated to drought, as some of the highest dust fluxes in the last decade occurred in 2005 following a wet winter (Reheis and Urban, 2011).…”
Section: Heterogeneity Of Emissionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also a major geomorphological factor for land degradation in arid regions [18]. High concentrations of dust at the local level may indicate agricultural soils are being degraded by the loss of fine particles [19]. Many previous studies have shown a positive correlation between drought years and increased dust emission [18,20], while others indicated the entry of dust in the atmosphere occurs once the freshly deposited sediment brought by the intense storms becomes desiccated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies about the origin, transport, and deposition of desert dust are available [19,23,28,33,34], a detailed understanding of the climatological and meteorological characteristics that influence dust event frequency and magnitude for sub-regions of the southwestern region of the U.S. are still lacking. This type of knowledge is needed to understand the regional and local dust climatology.…”
Section: Introductionmentioning
confidence: 99%